Sclerosing Extramedullary Hematopoietic Tumor: A Case Report - Dapeng Wang MD, PhD; Eduardo Castro MD; Arundhati Rao MD, PhD; Christopher Michael McPhaul MD (SAGE Publishing, 2020)
Sclerosing extramedullary hematopoietic tumor (SEMHT) is a rare disease that was originally named fibrous hematopoietic tumor or myelosclerosis. The process typically occurs in patients with a history of chronic myeloproliferative disorders and may afflict the skin, lung, breast, gastrointestinal tract, breast, kidney, lymph node, and thyroid gland. In this article, we report the case of a 37-year-old female with more than 5 years history of acute B-cell lymphoblastic leukemia who presented with right upper quadrant pain and tenderness. Computed tomography scan showed multiple new ring-enhancing low-density lesions within the right and left hepatic lobes. A computed tomography-guided liver core biopsy was performed on one of the new liver lesions and showed extramedullary hematopoiesis with atypical megakaryocytes and sinusoidal capillarization with associated fibroblastic proliferation. Numerous atypical megakaryocytes were scattered in the background of haphazard collagen deposition. No significant blasts or a leukemic process were identified. Bone marrow aspiration and biopsy showed extensive reticulin fibrosis (MF-3), trilineage dysplasia, increased blasts (10% to 19%), and hypercellularity (close to 100%), which was consistent with MDS-EB-2. Cytogenetics was reported as follows: 44~46,XX,-3,add(3)(p13),-5,-6,-7,17,del(17)(p12),+1~5mar[cp9]/46,XX. Molecular analysis was negative for both JAK2 V617F and CALR exon 9 activating mutations. In summary, we contributed a new case of SEMHT diagnosis in a synchronous presentation with poor clinical evolution associated chromosome 7 deletion and intact JAK2 and CALR exon 9. Care should be taken when diagnosing intraabdominal and retroperitoneal soft tissue masses with the history of hematological disorders.